Contesting deep sea oil: Politicisation–depoliticisation–repoliticisation. (May 2019) - Bond, Sophie; Diprose, Gradon; Thomas, Amanda C
Between 2010 and 2017, the New Zealand Government undertook a range of subtle yet disturbing tactics to create a legislative environment that enabled deep sea oil exploration. This included forms of public endorsement, policy documents and legislative change that prioritised further oil development in the country to create a certain common-sense around increased fossil fuel extraction. In response, a range of communities and autonomous Oil Free groups have emerged to contest both the legislative changes and this underlying common-sense. We draw on this example to respond to calls within geography and political science literature to situate analysis of contemporary politics in empirical contexts. We use Rancière's thought combined with the frames of politicisation, depoliticisation and repoliticisation to explore the entangled nature of government and oil industry actions, and community climate change activism. We argue that while there were clearly attempts by government and the oil industry to close down spaces of dissent and limit debate around fossil fuel development to technocratic questions of health and safety, the effects of attempts at closure are paradoxical. Such attempts at closure are always incomplete and at times, mobilise people to contestatory action. We show how activists have strategically drawn on certain discourses to exert claims of, and for, equality in public debates around the pressing issue of climate change.